2009
DOI: 10.1158/1078-0432.ccr-09-0055
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 and GATA5 are Potential Tumor Suppressors and Biomarkers in Colorectal Cancer

Abstract: Purpose: The transcription factors GATA4 and GATA5 are involved in gastrointestinal development and are inactivated by promoter hypermethylation in colorectal cancer. Here, we evaluated GATA4/5 promoter methylation as potential biomarkers for noninvasive colorectal cancer detection, and investigated the role of GATA4/5 in colorectal cancer. Experimental Design: Promoter methylation of GATA4/5 was analyzed in colorectal tissue and fecal DNA from colorectal cancer patients and healthy controls using methylation-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 29 publications
10
144
0
Order By: Relevance
“…Functionally, they activate the promoter of tumor suppressor genes and serve as tumor suppressors, the lost expression of which accelerates the development of colon cancer. For example, colon cells with GATA4 and 5 expression had reduced colony formation, proliferation, migration, invasion and anchor growth (12). In a previous study, GATA4 and GATA5 expression was lost in HepG2 cells and GATA4 and GATA5 transfection experiments inhibited tumor cell growth and colony formation, but induces tumor cell apoptosis.…”
Section: A B C D Ementioning
confidence: 88%
See 2 more Smart Citations
“…Functionally, they activate the promoter of tumor suppressor genes and serve as tumor suppressors, the lost expression of which accelerates the development of colon cancer. For example, colon cells with GATA4 and 5 expression had reduced colony formation, proliferation, migration, invasion and anchor growth (12). In a previous study, GATA4 and GATA5 expression was lost in HepG2 cells and GATA4 and GATA5 transfection experiments inhibited tumor cell growth and colony formation, but induces tumor cell apoptosis.…”
Section: A B C D Ementioning
confidence: 88%
“…The present study also demonstrated that GATA5 promoter methylation was more frequent in older patients, indicating that GATA5 promoter methylation may be an independent risk factor for older HCC patients. GATA4 and 5, as transcription factors, are involved in normal cell growth and also in adrenal gland, lung, ovary and colorectal cancer development (12). Functionally, they activate the promoter of tumor suppressor genes and serve as tumor suppressors, the lost expression of which accelerates the development of colon cancer.…”
Section: A B C D Ementioning
confidence: 99%
See 1 more Smart Citation
“…For example, promoter hypermethylation is associated with the silencing of various cancer-related genes (14,15), and aberrant methylation of the CpG islands of genes in stool and serum/plasma can be used as a molecular marker for detection of colorectal tumors (16)(17)(18)(19)(20). On the contrary, because DNA methylation is an early event (21)(22)(23), it does not enable one to distinguish between premalignant lesions and invasive tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, methylation markers can be useful for early detection of cancer. For instance, presence of TFPI2 or GATA4 methylation in stool DNA has reasonably high predictive value of colorectal cancer and can be used as a non-invasive screening tool coupled with conventional screening methods [165,166].…”
Section: Biomarker Developmentmentioning
confidence: 99%